(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Surveillance imaging after complex pelvic reconstruction for Ewing’s sarcoma (ES) often presents diagnostic challenges due to reactive skeletal changes. This report presents the case of a 34-year-old male with left hemipelvic Ewing’s sarcoma who underwent 17 cycles of chemotherapy followed by level I internal hemipelvectomy and reconstruction with a rod-and-screw construct and bone cement. A surveillance bone scan in June 2025 suggested osteoblastic recurrence in the left acetabulum and femoral neck. Subsequent FDG PET-CT demonstrated no focal hypermetabolic activity at these sites, identifying the bone scan findings as false positives caused by chronic remodeling and inflammation. This observation once again proves superior specificity of FDG PET-CT over bone scintigraphy, particularly in the presence of orthopedic hardware. Bangladesh J. Nuclear Med. 29(1): 125-127, 2026